Monitoring System for Sea Surface Temperature and Wind Speed in FADs Based on the Internet of Things - Hidayat, Andre Alfian; Angmalisang, Ping Astony; Bara, Robert Antonius; Sumilat, Deiske Adeliene; Luasunaung, Alfret; Warouw, Veibe (Universitas Nahdlatul Ulama Blitar, 2023)
Sea Surface Temperature (SST) is the temperature of the water measured at sea level. SST is a crucial marine parameter that influences the weather and climate in Indonesia. The value of sea surface temperature will be very closely related to factors such as the depth of measurement from sea level, the intensity of sunlight received, season, weather, water depth, air circulation, and cloud cover. This study aims to design a prototype tool to measure wind speed and sea surface temperature parameters. The components used are the DS18B20 sensor, JL-FS2 sensor, Arduino Mega 2560, and the SIM900a GSM Module. The system is displayed in real-time via the Thingspeak website, accessed via a PC or smartphone. The DS18B20 sensor, as a sea surface temperature sensor, can measure these parameters by looking at the trend of changing day and night temperatures. The JL-FS2, as a wind speed sensor, has been able to measure wind speed parameters during field tests at FADs.